Gorga Carving Art is A Creative Product of Economic Value to Increase Youth Production in Pansur Napitu Village, Siatas Barita District, North Tapanuli Regency - Tampubolon, Flansius; Sinulingga, Jekmen (Universitas Negeri Medan, 2024)
This dedication aims to overcome the decline in youth's interest and understanding of gorga carving in Pansur Napitu Village and develop the economic potential of traditional art. This decline in interest is due to a lack of knowledge, skills, and understanding of the economic value of gorga carving. This proposal will actively engage youth through training and empowerment programs. Training will focus on an introduction to gorga carving, carving techniques, and the application of creative design. Youth will be given knowledge about cultural values, history, and the importance of preserving the art of gorga carving. In addition, youth will be trained in aspects of product development and marketing. They will be taught about the use of quality materials, the development of attractive designs, and effective marketing strategies. With this understanding, the youth in Pansur Napitu Village will be able to produce gorga carving products that have high economic value. In implementing the program, cooperation with local governments, cultural institutions, and creative industry players will be a key factor. Support and synergy with related parties will facilitate access to resources, market opportunities, and networks that can support the development of gorga carving products, Program evaluation and monitoring will be carried out regularly to measure the success and impact that has been achieved. With effective training and empowerment, it is expected that the youth's interest in gorga carving will increase, their skills will be improved, and creative products of economic value will be produced, thus having a positive impact on the youth and the Pansur Napitu Village community.